A comparison of predictive control strategies for a highly segmented injection mold tempering. (18th March 2021) - Hopmann, Ch.; Kahve, C.E.; Schmitz, M.; Röbig, M.
Abstract: High precision, warpage free injection molded parts are highly in demand despite posing a great challenge. According to the pvT-behavior of the polymer, local variations of temperatures and pressures lead to inhomogeneous shrinkage which results in warpage. Since the pressure is dependent on the flow path, a homogenization of the specific volume is aimed by controlling the local mold temperatures. Therefore, a mold with 18 individually controllable tempering zones was developed, each zone equipped with ceramic heating elements and liquid CO2 expansion chambers. Due to the high mass of the mold, thermal processes underlie significant delays. The precise actuation of the tempering zones therefore requires a suitable control strategy. Two control strategies for the tempering zones were investigated on a basis of experimental trials. The tempering zones were initially controlled by a PID controller since it is easy to use and has low hardware requirements. To yield superior control precision, a model predictive control approach (MPC) has been recently developed and implemented, based on a discretized one-dimensional Fourier heat equation. The control accuracy of both control strategies was tested with an asymmetrical mold tempering experiment, which showed that the MPC is far more precise than the PID control approach. Highlights: Specific volume can be controlled precisely with local temperature manipulations Control precision and reproducibility of the MPC is superior to a PID-controller Warpage of specimens could be controlled precisely with the MPC tempering actuation